Pulmonary hypertension after bone marrow transplantation in children. Issue 5 (21st November 2019) - Levy, Marilyne; Moshous, Despina; Szezepanski, Isabelle; Galmiche, Louise; Castelle, Martin; Lesage, Fabrice; Dupic, Laurent; Neven, Bénédicte; Fischer, Alain; Blanche, Stéphane; Bonnet, Damien
Introduction: Pulmonary hypertension is a rare but important cause of mortality after haematopoietic stem cell transplantation (HSCT) in children. This complication is poorly characterised in the literature. We report here a series of children who developed pulmonary hypertension after HSCT. Methods: Between January 2008 and December 2015, we retrospectively analysed 366 children who underwent HSCT (age range 0.5–252 months; median 20.3 months). During the post-HSCT course, echocardiography scans motivated by respiratory symptoms identified 31 patients with elevated tricuspid regurgitation velocity (>2.8 m·s −1 ), confirmed when possible by right heart catheterisation (RHC). Results: 22 patients had confirmed pulmonary hypertension with mean±sd pulmonary arterial pressure 40.1±10 mmHg (range 28–62 mmHg) and pulmonary vascular resistance 17.3±9.2 Wood Units (range 8–42 Wood Units). Among the 13 responders at reactivity test, only one patient responded to calcium channel blockers. Seven patients (32%) died. 15 pulmonary hypertension patients were alive after a mean±sd follow-up of 6.5±2.3 years (range 2–10 years). All survivors could be weaned off pulmonary hypertension treatment after a median follow-up of 5 months (range 3–16). The delay between clinical symptoms and initiation of pulmonary hypertension therapy was significantly longer in patients who subsequently died (mean±sd 33.5±23 days; median 30 days) than in survivors (mean±sd 7±3 days) (p<0.001). Conclusion: Pulmonary hypertension is a severe complication of HSCT with an underestimated incidence and high mortality. Aggressive and timely up-front combination therapy allowed normalisation of pulmonary pressure and improved survival. Pulmonary hypertension is a rare and severe complication of haematopoietic stem cell transplantation in children, with a high mortality if misdiagnosed. Early diagnosis and treatment allow rapid clinical improvement with normalisation of PAP in most cases. http://bit.ly/2KXyhNN